Functional outcome of proximal fibular grafting after wide resection of distal radius tumour in HUSM from year 2000 to 2013 - Yin, Choo Chin (2016)
INTRODUCTION : Distal radius bone tumour surgery is a complicated and challenging procedure which includes resection of the affected bone and reconstruction of the bony defect. Several reconstructive procedures have been described including vascularized and non-vascularized fibular graft, osteoarticular allograft, prosthetic replacement and ulnar translocation. The proximal fibular graft was used in order to preserve better wrist function due to its similarity in shape and size to the distal radius. The aim of this study is to evaluate and compare the functional outcome between total wrist fusion and wrist reconstruction with proximal fibular grafting after wide excision of distal radius tumour by using Musculoskeletal Tumor Society scoring system (MSTS). METHODS : This study was a cross-sectional, single intervention and retrospectively assessed the selected eleven patients with distal radius bone tumour who had wide excision and reconstructive surgery done with proximal fibular autograft that fulfilled the inclusion and exclusion criteria. All the patients recruited in this study were from year 2000 to 2013 and sampled into two groups; the wrist reconstruction and total wrist fusion groups. Functional outcome was evaluated and compared by using Musculoskeletal Tumour Society scoring system (MSTS). Hand grip strength and union rate were assessed by Jamar hand dynamometer and plain radiographs respectively. RESULTS : There were 6 patients underwent wrist reconstruction procedure and 5 patients underwent total wrist fusion. The mean age of patients was 36.55 years old. Mean follow up period was 6.3 years. There were 9 patients with Campanacci grade II to grade III giant cell tumours, 1 patient with osteosarcoma and 1 patient with aneurysmal bonecyst in this study. Overall musculoskeletal tumor society (MSTS) score range from 70% to 93.3%, with 4 good and 7 excellent results. The mean MSTS score for wrist reconstruction group was 24.83 (82.78%) and total wrist fusion group was 23.4 (78.0%). Average grip strength compared to the contralateral hand was 60.0% for total wrist fusion which was better than wrist reconstruction, 58.07%. Radiofibular union occurred in 8 out of 11 cases. The union rate for wrist reconstruction was 83.3% whereas for total wrist fusion was 60%. Excluding the 3 non-union cases, average time for union was 18.4 weeks for the wrist reconstruction and 18.7 weeks for the total wrist fusion. There was no tumour recurrence and all the patients were disease free. CONCLUSION : Proximal fibular grafting after wide excision of distal radius bone tumour had good to excellent MSTS score for both wrist reconstruction and total wrist fusion. The only significant finding was the scoring for pain component in MSTS was more superior in total wrist fusion. However, there was no significant difference for the overall MSTS score between these procedures. The most commonly encountered complication was fibulocarpal subluxation which found in wrist reconstruction group.